Productivity and competitiveness of the Western Balkan countries: An analysis based on the wiiw Western Balkan Productivity Database - Oliver Reiter; Monika Schwarzhappel; Robert Stehrer (The Vienna Institute for International Economic Studies (wiiw), 2020)
This policy brief provides results regarding productivity levels and dynamics in the Western Balkan countries in a comparative perspective, drawing on the newly established wiiw Western Balkan Productivity Database. The database provides time series of value added, gross output and intermediate inputs as well as labour productivity and unit labour costs, based on data collected from national statistical institutes. We present the most important indicators comparing productivity performance of the Western Balkan countries with Bulgaria and Romania (which became EU Members in 2007) and Croatia (which became an EU Member in 2013). Our results indicate that all Western Balkan countries have surpassed the level of productivity of Bulgaria in 2007 but productivity growth has stalled since the crisis. Unit labour costs growth has been low, though from a relatively high level (compared to neighbouring countries). These results make the case that advancing the EU accession process for the Western Balkan countries is both viable and necessary
Keywords: E01; O11; O40; O47; 330; Productivity; unit labour costs; Western Balkan countries; accession